Barreiras e potenciais facilitadores para implantação de compras sustentáveis na Universidade Federal de São Carlos - Assandre, Junior Aparecido (2016)
Issues of environmental concern and changes in the interaction between society and the environment gained prominence in recent years. In this context public educational institutions, among them the Federal Universities should assume a position of spread of initiatives that promote consumption patterns and more sustainable production and serve as a mirror to society, as a vital role in social and professional training of individuals, can significantly influence the aspects of culture, ethics and citizenship. Universities are driving new standards, whether as a result of the provision of social services to them is charged or leading by example by exercising the employer function and consumers on a large scale. Before relevant scenario the general aim of this study was to analyze the barriers and facilitators to implementation of sustainable procurement at the Federal University of São Carlos. The survey was conducted as to its purpose and exploratory and descriptive of its overall objectives. Having a qualitative approach which included multiple forms of research and used as a method action research, in order to understand and intervene in the situation. Through this method were three bidding processes with sustainability criteria in UFSCar. The main results revealed that even though a team of experienced bidding the institution should overcome barriers as a market incipient supplier, products and services with higher costs, lack of involvement of the participating units of the process, low degree of planning and the need for policy institutional sustainable procurement, for effective implementation of this type of acquisition.